2018
DOI: 10.1002/jcb.27947
|View full text |Cite
|
Sign up to set email alerts
|

PKM2 promotes glucose metabolism through a let‐7a‐5p/Stat3/hnRNP‐A1 regulatory feedback loop in breast cancer cells

Abstract: Tumor cells metabolize more glucose to lactate in aerobic or hypoxic conditions than normal cells. Pyruvate kinase isoenzyme type M2 (PKM2) is crucial for tumor cell aerobic glycolysis. We established a role for let‐7a‐5p/Stat3/hnRNP‐A1/PKM2 signaling in breast cancer cell glucose metabolism. PKM2 depletion via small interfering RNA (siRNA) inhibits cell proliferation and aerobic glycolysis in breast cancer cells. Signal transducer and activator of transcription 3 (Stat3) promotes upregulation of heterogeneous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 40 publications
2
31
0
Order By: Relevance
“…The study by Lin et al [35] indicates that palmitic acid limits glycometabolism through the attenuation of STAT3 pathway in hepatocellular carcinoma. Furthermore, STAT3 signaling participates in the pyruvate kinase isoenzyme type M2-mediated glycolysis of breast cancer cells [36]. Our data herein suggested STAT3 played a crucial role in HK2 expression and glucose metabolism of human CRC cells.…”
Section: Discussionmentioning
confidence: 61%
“…The study by Lin et al [35] indicates that palmitic acid limits glycometabolism through the attenuation of STAT3 pathway in hepatocellular carcinoma. Furthermore, STAT3 signaling participates in the pyruvate kinase isoenzyme type M2-mediated glycolysis of breast cancer cells [36]. Our data herein suggested STAT3 played a crucial role in HK2 expression and glucose metabolism of human CRC cells.…”
Section: Discussionmentioning
confidence: 61%
“…There is growing evidence that miRNAs can regulate glycolysis directly by regulating the expression of genes encoding for glycolysis pathway or indirectly by controlling the expression of oncogenes and tumor suppressor genes involved in glycolysis. Hsa-let-7a has been shown to regulate glycolysis in various cancers [7072]. In addition, SIRT2, which was downregulated by hsa-miRNA-1972 has been shown to be a potent regulator of glycolysis [73].…”
Section: Discussionmentioning
confidence: 99%
“…Since the discovery of Warburg effects, metabolism is strongly linked with proliferation of cancer cells. It has been suggested that let-7a-5p, Stat3, and hnRNP-A1 form a feedback loop to regulate PKM2 expression and modulate glucose metabolism in breast cancer cells, suggesting that inhibiting STAT3-related metabolism may inhibit breast cancer proliferation [42].…”
Section: The Role Of Stat3 In Breast Cancer Proliferation and Apoptosismentioning
confidence: 99%